COMPARATIVE ASSESSMENT OF LEISURE TIME ACTIVITIES OF CHILDREN AGED 11 TO 17 YEARS OLD WHO OFTEN AND RARELY USE DIGITAL DEVICES AND THE INTERNET - Roza T. Kamilova; Amangul Zh. Kurbanbaeva (Central Asian Journal of Medicine, 2025)
This article discusses the impact of digital devices and Internet use on children's leisure activities. The purpose of this paper was to assess the impact of digital devices and the Internet on children's daily and leisure time, physical activity, and leisure time activities. Material and methods. A questionnaire was conducted among 900 general education school pupils aged 11 to 17. Results. The results of the questionnaire show that children nowadays spend a lot of time engaged in the use of various digital devices, especially smartphones. They are also actively logging into social media sites such as Telegram, YouTube, Instagram, Snapchat, and TikTok. It is interesting to note that most children use gadgets in sitting positions and various situations, including transportation. They prefer to use cell phones, computers, laptops, and tablets but also show interest in reading activities. Digital devices do not have a significant impact on time spent on homework but may affect physical activity and time spent outdoors. Thus, the use of digital devices is an integral part of children's lives, but the diversity of children's interests and preferences should be considered. Conclusion. The questionnaire survey helped to obtain valuable information about what children do during their free time and what leisure preferences they have. Undoubtedly, these indicators determine the lifestyle and affect the health status of children.